Pelatihan Rukti Jenazah sebagai Strategi untuk Meningkatkan Kepedulian Sosial di Lingkungan Perkotaan - Puspitasari, Evi; Murtiningsih, Sri Rejeki; Zulfa, Auliya Failaih; Setiawan, Ferry (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
The social phenomenon of urban communities that are prone to individualism influences low social awareness. Rukti Jenazah as an activity that captures the manifestation of social and cultural values in society is starting to be rarely found in urban communities. Generally, they rely on third party services for corpse care rather than doing it collectively. This shows that community activities that require a sense of social awareness face real challenges in an era where human relationships are starting to grow distant. This certainly needs to be a concern for all parties. By involving 26 members of the organization as participants, the activity was carried out in three stages, namely input session, discussions, and direct practice with media that had been prepared by the community service team. The series of activities went smoothly and proved successful in increasing participants’ understanding of the attitude of social awareness and how it is manifested through this activity. This was shown through the average post-test score (49.69) which was higher than the average pre-test score (44.31). The average understanding of participants increased by 5.38 points. This is the basis for Branch Manager of Muhammadiyah Notoyudan to develop and expand the Rukti Jenazah training program as a sustainable strategy in increasing social awareness and solidarity between residents, as well as a model that can be applied in other areas with similar problems.